Acta Mathematica Sinica, English Series - Ma, Zhi-Ming.; Zhang, Liqun; Sun, Yunzhi; SpringerLink (Online service) (Beijing : Institute of Mathematics, Chinese Academy of Sciences and Chinese Mathematical Society : Imprint: Institute of Mathematics, Chinese Academy of Sciences and Chinese Mathematical Society, co-published with Springer.)
Acta Mathematica Sinica, established by the Chinese Mathematical Society in 1936, is the first and the best mathematical journal in China. In 1985, Acta Mathematica Sinica is divided into English Series and Chinese Series. The English Series is a monthly journal, publishing significant research papers from all branches of pure and applied mathematics. It provides authoritative reviews of current developments in mathematical research. Contributions are invited from researchers from all over the world.
Keywords: Mathematics; Mathematics, general